Critical CALL – Proceedings of the 2015 EUROCALL Conference, Padova, Italy 2015
DOI: 10.14705/rpnet.2015.000308
|View full text |Cite
|
Sign up to set email alerts
|

The alignment of CMC language learning methodologies with the Bridge21 model of 21C learning

Abstract: This paper explores the intersection of learning methodologies to promote the development of 21st century skills with the use of Computer-Mediated Communication (CMC) tools to enhance language learning among adolescent learners. Today, technology offers a greater range of affordances in the teaching and learning of second languages while research shows that student classrooms still continue to concentrate on linguistic competences rather than communicative competences (Gilmore, 2011). The Bridge21 model, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Other studies examined how ICTs can facilitate language learning and teaching if a harmonious ICT policy is implemented (e.g., Benini, 2014) and can facilitate European collaboration at secondary level (e.g., Bauer et al, 2015;Masterson, 2018Masterson, , 2020. Benini (2014) explored the use of ICTs in two different schools -School A where the use of ICTs is heavily promoted (all students had notebooks or tablets) while School B had a more traditional approach (one computer lab for the entire school).…”
Section: Secondary Schoolmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies examined how ICTs can facilitate language learning and teaching if a harmonious ICT policy is implemented (e.g., Benini, 2014) and can facilitate European collaboration at secondary level (e.g., Bauer et al, 2015;Masterson, 2018Masterson, , 2020. Benini (2014) explored the use of ICTs in two different schools -School A where the use of ICTs is heavily promoted (all students had notebooks or tablets) while School B had a more traditional approach (one computer lab for the entire school).…”
Section: Secondary Schoolmentioning
confidence: 99%
“…It leads to inadequate ICT training for MFL and therefore prevents teachers from integrating ICTs in the MFL classroom. Bauer et al (2015) investigated how learning technologies – that is, computer-mediated communication – could foster distance learning for students collaborating between Ireland and Germany by increasing oral production and comprehension of authentic documents in the L2. Masterson (2018) showed that using eTwinning – an online collaboration tool for secondary schools in the European Union – with an experiential learning model enabled students to develop cross-cultural awareness and knowledge.…”
Section: Modern Foreign Languagesmentioning
confidence: 99%
“…Yet, digital technology alone cannot be depended on to produce classroom dynamic. Students need to be guided by interesting task integrated with contemporary artifact in a constructive environment (Bauer, Devitt, & Tangney, 2015).Thus, successful integration of technology International Journal of Education ISSN 1948-5476 2019 into education needs changes in teaching and learning strategies. Appreciative Inquiry could be an ideal theoretical and practice guide for today's teachers.…”
Section: Oral Linguistic Performancementioning
confidence: 99%
“…While Autonomy helps language learners to get rid of the shyness, anxiety and fear of speaking a new language through being responsible of their own learning, self-reflection stresses the necessity of serious and deep thought about one's oral performance through monitoring and analyzing features that often go unnoticed during production. Today, technology supports such change through offering a wide range of facilities, tools and apps in foreign languages instruction (Bauer, Devitt & Tangney, 2015;Dupagne, Stacks & Giroux, 2007;Gilmore, 2011, Madhany, 2006). Yet, digital technology alone cannot be depended on to produce classroom dynamic.…”
Section: Introductionmentioning
confidence: 99%